Chemical heterogeneity enables austenite stabilization in a Si-/Al-free Fe-0.2C-2Mn steel. (September 2022) - Zhang, Chaofan; Liu, Chenxi; Guo, Hui; Sun, Shaoheng; Chen, Hao; Liu, Yongchang; Ding, Ran
Abstract: A chemical heterogeneity of Mn is introduced into the parent austenite of a Fe-0.2C-2Mn steel. The Mn-rich regions in the parent austenite is substantially stabilized by a promoted C partitioning during the austenite to ferrite transformation, without which these regions cannot be preserved as retained austenite. Following this strategy, a multiphase microstructure is achieved which presents a better combination of strength (ultimate strength of 977 MPa) and ductility (uniform elongation of 17.9%) as compared with that of other Si- or Al-added AHSSs of similar compositions. The results here suggest an alternative, yet a simple route, to acquire retained austenite in advanced high strength steels without the need of Si and Al alloying. Graphical abstract: Image, graphical abstract